Oribatid mites in a succession of permafrost soils in Central Yakutia - Mikhail V. Yakutin; Vladislav S. Andrievskii; Franz Conen; Alexander N. Puchnin (Arctic, Antarctic, and Alpine Research)
Thermokarst troughs formed on ice-rich ground in Central Yakutia harbor contrasting soils that have developed from lake silt through a marsh stage to meadow and steppe-like soils. Associated processes result in radical transformations of an important component of the decomposer community in the biological cycle—the oribatid mites community. During the transition of soil from a Histic Reductaquic Cryosol to a Gleyic Cryosol and, finally, to a Turbic Chernic Cryosol, the number of species increased from three to six to thirteen. Total abundance of oribatid mites increased from 1,600 m−2 (±265) to 2,442 m−2 (±328) to 8,640 (±588) m−2. A characteristic feature of these permafrost soils was the considerable similarity of the populations in the Gleyic Cryosol and the Turbic Chernic Cryosol and their negligible overlap with the oribatids population of the Histic Reductaquic Cryosol. The peculiarity of the Histic Reductaquic Cryosol is manifested both in quantitative parameters of the communities and in their qualitative characteristics, such as the dominance structure and the sets of species with different ecological preferences.